Pengaruh Konten Tiktok Hanif Alim dalam Meningkatkan Keterampilan Komunikasi Gen-Z untuk Mencari Kerja - Valerie, Felicia; Nurhajati, Lestari (Jurnal Pewarta Indonesia, 2024)
This research focuses on the influence of Hanif Alim's TikTok content on the communication skills of Gen-Z in job seeking. With the rapid growth of internet users, social media platforms like TikTok have become important for sharing information. The research aims to understand the impact of such content on the communication skills of Gen-Z in the context of employment. Thus, this study explores how TikTok affects their job readiness. The research utilizes a survey method within a quantitative analysis approach. A questionnaire was employed to collect data from 100 Gen-Z respondents following the TikTok account @hanifalim in Jakarta. The questions were related to Likert scale indicators with 5 points. The questionnaire was distributed via Google Form to the account followers through direct messages (DMs) to solicit participation. Consequently, it can be inferred that there is an influence of Hanif Alim's TikTok Content (X) in Enhancing the Communication Skills of Gen-Z in Job Seeking. The influence of the variable Hanif Alim's TikTok Content (X) on the variable Enhancing the Communication Skills of Gen-Z in Job Seeking (Y) is 77.5%. The remaining percentage is influenced by other factors not identified in this study.